2016
DOI: 10.1186/s40478-016-0359-7
|View full text |Cite
|
Sign up to set email alerts
|

Axonal plasticity underpins the functional recovery following surgical decompression in a rat model of cervical spondylotic myelopathy

Abstract: Cervical spondylotic myelopathy (CSM) is the most common spinal cord disorder and a major cause of disability in adults. Improvements following surgical decompression are limited and patients often remain severely disabled. Post mortem studies indicate that CSM is associated with profound axonal loss. However, our understanding of the pathophysiology of CSM remains limited.To investigate the hypothesis that axonal plasticity plays a role in the recovery following surgical decompression, we adopted a novel prec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
54
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(57 citation statements)
references
References 53 publications
2
54
0
1
Order By: Relevance
“…Although direct comparison between the disease severity and the MVF, the AVF and the g-ratio was not performed in this study, another study has revealed that MRI shows disease progression more often than clinical measures do, possibly because incremental injury does not necessarily manifest with neurological/functional deficits 37 . Promoting axonal plasticity may be useful to improve neurological function in CSM 38 , so estimation of microstructural changes in the spinal cord by MR imaging including the MVF, the AVF and the g-ratio will play an important role for patient management, with development of regenerative medicine.…”
Section: Discussionmentioning
confidence: 99%
“…Although direct comparison between the disease severity and the MVF, the AVF and the g-ratio was not performed in this study, another study has revealed that MRI shows disease progression more often than clinical measures do, possibly because incremental injury does not necessarily manifest with neurological/functional deficits 37 . Promoting axonal plasticity may be useful to improve neurological function in CSM 38 , so estimation of microstructural changes in the spinal cord by MR imaging including the MVF, the AVF and the g-ratio will play an important role for patient management, with development of regenerative medicine.…”
Section: Discussionmentioning
confidence: 99%
“…However, loss of external anal sphincter muscle mass was recovered 4 weeks after balloon distention. Recovery of neural damage in rats has previously been reported by studies in the field of experimental neuronal damage models . They showed that neuroplasticity in the subcortical regions in rats allows recovery from stroke and spinal cord injuries through neural remodeling.…”
Section: Discussionmentioning
confidence: 81%
“…The dura mater underneath was carefully separated from the lamina to avoid a tear and cerebral spinal fluid (CSF) leak. In the animals assigned to the sham operation group, the implantation passed through the dorsal epidural space [ 34 ]. Multilayer tissue closure was then performed [ 5 ].…”
Section: Methodsmentioning
confidence: 99%